"Scare the Bear" with these tips for dealing with workplace bullying. Issue 8 (8th April 2022) - Hodges, Dawn Z.
Abstract : Not long ago, I had lunch with a former colleague. She was recounting an incident that happened at her vacation home in Florida when she was cooking a rather fragrant meal. She looked out on the patio to see a black bear tear through the screen and come look in her back door. She called animal control. They said they don't relocate the bears because "they don't do well in the wild." So, what was she to do? "Scare the bear, " they told her.